Analisa Terhambatnya Proses Discharge Pada Cargo Pump Di Kapal MT. Karmila - Darmana, Eka; Supriyadi, Agus (Universitas Ivet, 2021)
PT. Pertamina appointed the MT ship. Karmila becomes a bunker ship, which is useful for supplying MFO fuel to Pertamina's ships and Pertamina's charter ships operating in the Dumai port area. So that the cargo pump plays a very important role in the fuel supply process. Obstruction of the discharge process will result in a decrease in the performance of the cargo handling process which will hamper ship operational activities. The method used is a case study with a qualitative descriptive analysis approach. Data collection obtained by direct observation at MT. KARMILA which is a ship owned by PT. PERTAMINA and direct interviews with the ship's crew. In addition, data sources are also obtained from the instruction manual, SOPs on board and references from articles related to pumping rates. The results of this study state that the problems that occur when the cargo supply bunker discharge is caused by several factors such as difficulty in adjusting the pumping rate for the supply bunker according to pipe capacity, the temperature increase of the electro motor cargo pump (overheating), the high initial load so that the generator is unstable, damage to the connection hose to the supply bunker. These things cause problems when the cargo discharge process for supply bunkers. One solution to overcome these problems is to control the rotation of the electro motor cargo pump using an inverter so that the pumping rate can be controlled as needed so that excess load and pressure can be avoided.